2022
DOI: 10.1136/bmjopen-2021-057817
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden and its associated factors among family caregivers of persons with dementia in Shanghai, China: a cross-sectional study

Abstract: ObjectiveTo assess the level of caregiver burden and factors associated with it among family caregivers of persons with dementia (PWD) living in communities of Shanghai, China.DesignCross-sectional study.SettingCommunities in Hongkou District of Shanghai, China.ParticipantsA random sample of 109 older adults with dementia and their primary family caregivers.Main outcome measureCaregiver burden measured by the Caregiver Burden Inventory (CBI), and the Caregivers’ depressive symptom measured by the simplified Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Of the 23 studies, 8 ( 14 , 21 – 27 ) (34.8%) were in English and 15 ( 15 – 17 , 28 – 39 ) (65.2%) were in Chinese. In addition, 14 studies ( 14 – 16 , 21 , 23 , 27 – 29 , 32 , 34 – 39 ) (60.9%) employed Caregiver Burden Inventory (CBI), 7 ( 17 , 22 , 24 26 , 31 , 33 ) (30.4%) employed Zarit Burden Interview (ZBI), 1 ( 30 ) (4.3%) employed Family Burden Scale (FBS), and 1 ( 15 ) (4.3%) employed Perceived Stress Scale (PSS). This review included 4,076 participants, and the sample sizes ranged from 94 to 335.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 23 studies, 8 ( 14 , 21 – 27 ) (34.8%) were in English and 15 ( 15 – 17 , 28 – 39 ) (65.2%) were in Chinese. In addition, 14 studies ( 14 – 16 , 21 , 23 , 27 – 29 , 32 , 34 – 39 ) (60.9%) employed Caregiver Burden Inventory (CBI), 7 ( 17 , 22 , 24 26 , 31 , 33 ) (30.4%) employed Zarit Burden Interview (ZBI), 1 ( 30 ) (4.3%) employed Family Burden Scale (FBS), and 1 ( 15 ) (4.3%) employed Perceived Stress Scale (PSS). This review included 4,076 participants, and the sample sizes ranged from 94 to 335.…”
Section: Resultsmentioning
confidence: 99%
“…Studies ( 15 , 30 , 33 , 37 ) have indicated that 70.3–100% of family caregivers bear the burden of care. In addition, primary family caregivers in 14 studies ( 14 , 16 , 22 , 23 , 26 , 28 – 30 , 32 – 37 ) (60.9%) were offspring or other relatives and in six studies ( 15 , 24 , 25 , 27 , 31 , 38 ) (26.1%) were spouses, but three studies ( 17 , 21 , 39 ) (13%) were failed to mention the proportion of caregivers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the improved perceived social support will decrease the caregiving burden. Recent evidence also suggests that social support is a determining factor in the caregiving burden (Tao et al, 2022;Liu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%